Knowledge, attitude, and practice regarding venous thromboembolism prophylaxis: A multicenter cross-sectional study of medical staff in Guinea - Xinnong Liu; Soriba Naby Camara; Mamady Diakite; Denis Bernard Raiche; Zhujiazi Zhang (PLoS ONE, 2025)
Objectives To investigate the awareness of medical staff regarding venous thromboembolism (VTE) prophylaxis in Guinea. Methods The survey was completed from June 1, 2023 to August 1, 2023 through filling out self-designed questionnaire including four parts containing demographic data, knowledge, attitude, and practice regarding VTE prophylaxis. Cronbach’s alpha values were used to analyze the internal consistency of the questionnaire. The results were analyzed using chi-square tests at a 95% significance level. Results Of the 245 medical staff invited to participate in the survey, 211 (86.1%) responded. Cronbach’s alpha value of the questionnaire was 0.92. The overall correct response rate for knowledge was 61.5 ± 11.7%, and there were no significant differences between hospitals, sexes, professions, educational levels, departments, and working years (P > 0.05). The overall affirmative response rates for attitude and practice were 65.3% ± 18.4% and 74.8 ± 13.4%, respectively. The affirmative rate of nurses was higher than that of clinicians in the aspects of attitude (69.51 ± 20.2% vs. 63.0 ± 18.1%) and practice (82.1 ± 16.9% vs. 70.4 ± 10.8%); however, no significant difference was found (P > 0.05). Conclusions The knowledge level, attitude, and practice regarding VTE prophylaxis among medical staff in Guinea were generally poor. We suggest that medical institutions provide appropriate VTE prophylaxis-related trainings.